Nabi'nin Tuhfetü'l-Harameyn Adlı Seyahatnamesinin Edebi Kaynakları - Coşkun, Menderes (Kitabevi, 2001)
Nabi in his pilgrimage narrative called Tuhfetü'l-harameyn quotes a number of verses from such classical Persian and Turkish poets in order to compose the narrative in a prose style accepted in his period. Most of these quotations are from 15th century Persian poet Muhyi's Fütuhu'l-harameyn, which was also attributed to the distinguished poet Abdurrahman Cami for a long time. Despite of all these quotations, Nabi's narrative can not be regarded as an imitation of Muhyi's verse narrative Fütuhu'l-harameyn. Tuhfetü'l-harameyn undoubtedly remains original from the point if its content and prose style. Because it is a narrative based on Nabi's real journey to Urfa, Damascus, Jerusalem, Cairo and Mecca in the years 1089-1090/1678-79.
Literary Sources of Nabi' s Tuhfat al-Haramayn
Keywords: Nabi; Tuhfetü'l-harameyn; Divan Edebiyatı; Klasik Türk Edebiyatı; Seyahat Kitabı